1991
DOI: 10.1002/eji.1830211205
|View full text |Cite
|
Sign up to set email alerts
|

Homing receptors reexamined: mouse LECAM‐1 (MEL‐14 antigen) is involved in lymphocyte migration into gut‐associated lymphoid tissue

Abstract: Specific recognition molecules ("homing receptors") on lymphocytes are thought to direct selective entry of cells into different organs. The lectin-related cell adhesion molecule LECAM-1 has previously been supposed to mediate lymphocyte entry into peripheral lymph nodes and, partially, mesenteric nodes but not into Peyer's patches. Here we present evidence that in vivo the molecule is also implicated in homing of mouse lymphocytes to Peyer's patches and may have a more general role as homing receptor for high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 22 publications
3
40
0
Order By: Relevance
“…It is possible that the ␣4␤7 ϩ and L-selectin Ϫ ASC are bound to extravasate through flat-walled venules in the intestinal lamina propria, which constitutively express MAdCAM-1 but only little PLN addressin (8,10,36). ␣4␤7 ϩ and L-selectin ϩ ASC, on the other hand, may leave the circulation and migrate to more organized mucosal lymphoid tissues, such as mesenteric lymph nodes (MLN) and Peyer's patches, whose HEV express both MAd-CAM-1 and PLN addressin (36,37), and to which L-selectindependent homing has been documented (38). In accordance with this notion, our previous studies have shown that MLN harbor large numbers of vaccine-specific ASC after enteric immunization in monkeys (39).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the ␣4␤7 ϩ and L-selectin Ϫ ASC are bound to extravasate through flat-walled venules in the intestinal lamina propria, which constitutively express MAdCAM-1 but only little PLN addressin (8,10,36). ␣4␤7 ϩ and L-selectin ϩ ASC, on the other hand, may leave the circulation and migrate to more organized mucosal lymphoid tissues, such as mesenteric lymph nodes (MLN) and Peyer's patches, whose HEV express both MAd-CAM-1 and PLN addressin (36,37), and to which L-selectindependent homing has been documented (38). In accordance with this notion, our previous studies have shown that MLN harbor large numbers of vaccine-specific ASC after enteric immunization in monkeys (39).…”
Section: Discussionmentioning
confidence: 99%
“…New data suggest that both E-and P-selectin may participate in the neutrophil-mediated damage associated with ischemic reperfusion injury in the heart (56,163). Antibodies to L-selectin and soluble recombinant forms ofL-selectin have been used to demonstrate the participation ofthis molecule in a variety of animal models of homing and inflammation (25,26,164,165). Other recent observations may also lead to increased understanding ofselectin function in human disease processes.…”
Section: Selectins and Diseasementioning
confidence: 99%
“…4 In experiments using neutralizing anti-L-selectin monoclonal antibodies (mAbs) or mice that are genetically deficient in L-selectin, naive T lymphocytes do not home to PLNs, and primary T-cell responses to antigen are impaired. 1,5,6 L-selectin is shed from the cell surface by a proteolytic mechanism upon crosslinking by mAbs 7 or upon T-cell activation. 8,9 The signal transduction mechanisms leading to L-selectin cleavage are not yet defined.…”
Section: Introductionmentioning
confidence: 99%